(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Cerebral venous sinus thrombosis (CVST) is a rare form of stroke frequently underdiagnosed due to its variable clinical presentation which may be related to different pattern of dural sinus involvement. Objective: The purpose of the present study was to evaluate the clinical and radiological profiles of patients diagnosed with Cerebral Venous Sinus Thrombosis (CVST) and to categorize the findings based on their mode of presentation. Methodology: This cross-sectional study was conducted in the Department of Neurology at National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from January 2023 to May 2025 for a period of approximately two and half years. All the patients diagnosed as CVST, admitted at IPD were selected as study population. The patients were examined clinically and radiologically confirmed. Results: Of the total of 100 patients, majority of the patients were young adult (mean age 33.58 ± 13.47) with female predominance (76.0%). Headache was the most common presenting complaint (95.0%), followed by vomiting in (82%) and Impaired consciousness (43.0%). Focal deficit was found in 44.0% and papilledema 52.0% of participants. Majority of presented in the sub-acute phase (74%), while chronic presentations were relatively rare (5.0%). The majority of patients (79.0%) had multiple sinus involvement. The transverse sinus was the most frequently affected (83.0%) followed by Superior Sagittal Sinus (65.0%) and Sigmoid sinus (65.0%). Visual disturbances and papilledema were significantly more prevalent in the CVST patients with sub-acute presentation compared to the acute CVST patients (p = 0.002 and p = 0.001 respectively). Conclusion: In conclusion, cerebral venous thrombosis presents with diverse clinical features, often with overlapping symptoms across different stages. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):3-8